O18.6 A method to estimate the national prevalence of hiv-infection among female sex workers in zimbabwe by pooling data from multiplie respondent driven sampling surveys and programme consultations. (13th September 2015) - Fearon, E; Hargreaves, JR; Davey, C; Dirawo, J; Mushati, P; Cowan, FM
Abstract : Introduction: Respondent driven sampling (RDS) surveys are often used to estimate site-specific HIV-prevalence among female sex workers (FSW). Methods to combine data from multiple sites to estimate national or provincial HIV-prevalence are rarely described. Methodology: Using data from the Zimbabwean national FSW HIV prevention programme, working in 36 priority sites across all provinces, we estimated the average number of visits made by FSW to outreach sexual/reproductive health clinics each month at each site between January 2014–Dec 2014. We treated this variable as a proxy for the relative size of the FSW population at each site. We conducted RDS surveys with HIV testing among 200 FSW in 14 of the 36 sites, purposively selected. We used the RDS-2 analysis approach to estimate HIV prevalence in each of the 14 sites. We then combined data from the 14 sites, weighting each site by the proxy for FSW population size to provide an estimate of the national prevalence of HIV among FSW in Zimbabwe. Results: The HIV prevalence across sites ranged from 43 to 79%. The unweighted mean of the site-specific prevalences was 57.5% (95% CI 51.9–62.8%). The mean number of women visiting each site per month over 2014 ranged from 16 to 87. The weighted women visiting each site per month in 2014 mean of the site-specific HIV prevalences was 58.1% (95% CI 53.8.4–62.2%). Conclusions: HIV prevalence among FSW in Zimbabwe is very high but variable by site. We describe an approach to estimating national HIV prevalence from multiple site-specific surveys. Here, weighting made little difference to a mean approach though this may not always be the case. Several future refinements to the method proposed are possible and will be discussed. Disclosure of interest statement: The SAPPH-IRe trial is using Truvada donated by Gilead. We have no other relationships with commercial entities to disclose.